Mechanism of Dissolution Enhancement and Bioavailability of Poorly Water Soluble Celecoxib by Preparing Stable Amorphous Nanoparticles - Liu, Yinghui; Sun, Changshan; Hao, Yanru; Jiang, Tongying; Zheng, Li; Wang, Siling (Journal of Pharmacy & Pharmaceutical Sciences, 2010)
Purpose: Nanoparticle engineering offers promising methods for the formulation of poorly water soluble drug compounds. The aim of the present work was to enhance dissolution and oral bioavailability of poorly water-soluble celecoxib (CXB) by preparing stable CXB nanoparticles using a promising method, meanwhile, investigate the mechanism of increasing dissolution of CXB. Methods: CXB nanoparticles were produced by combining the antisolvent precipitation and high pressure homogenization (HPH) approaches in the presence of HPMC E5 and SDS (2:1, w/w). Then the CXB nanosuspensions were converted into dry powders by spray-drying. The effect of process variables on particle size and physical state of CXB were investigated. The physicochemical properties of raw CXB and CXB nanoparticles were characterized by scanning electron microscopy (SEM), X-ray powder diffraction (XRPD), X-ray photoelectron spectra (XPS), fourier transform infrared (FT-IR) spectroscopy, diffrential scanning calorimetry (DSC), as well as, measuring the particle size and contact angle. Additionally, the studies of in-vitro drug dissolution and oral bioavailability in beagle dogs of nanoparticles were performed. Results: The images of SEM revealed spherical CXB nanoparticles. The DSC and XRPD results indicated that the antisolvent precipitation process led to the amorphization of CXB. Under storage, the amorphous CXB nanoparticles showed promising physical stability. The XPS data indicated the amorphous CXB nanoparticles exhibited different surface property compared to raw CXB. Hydrogen bonds were formed between the raw CXB and HPMC E5 as proven by the FT-IR spectra. CXB nanoparticles increased the saturation solubility of CXB fourfold. CXB nanoparticles completely dissolved in the dissolution medium of phosphate buffer (pH 6.8, 0.5% SDS) within 5 min, while there was only 30% of raw CXB dissolved. The Cmax and AUC0–24h of CXB nanoparticles were approximately threefold and twofold greater than those of the Celecoxib Capsules, respectively. Conclusions: The process by combining the antisolvent precipitation under sonication and HPH was a promising method to produce small, uniform and stable CXB nanoparticles with markedly enhanced dissolution rate and oral bioavailability due to an increased solubility that is attributed to a combination of amorphization and nanonization with increased surface area, improved wettability and reduced diffusion pathway.